The Problematic of The Position of A Circular Letter In The Hierarchy of Legal Regulations (Study Of Circular Letter No: D/ED/PW.01/03/1992) In The Registration and Implementation of Marriages - Ridwan, Ridwan; Abidin, Muh Nur; Mustapha, Ahmad Sharifuddin (Advances in Humanities and Contemporary Studies, 2024)
The UUP is the result of the creation of a national marriage law.  It is the result of a unique blend of such laws that deeply respect differences based on religion and belief. If we track in the registration and implementation of marriage, there are problems that have not been resolved until now, referring to Article 42 of the UUP it is stated "A legitimate child is a child born in/as a result of a legal marriage" this provision is also regulated in the Compilation of Islamic Law Article 99. A legitimate child according to the Law is very clear, when a child is born in a legal marriage, it is the child of both parents, let alone proven by an authentic certificate as stated in Article 55 paragraph (1) of the Law, it is stated in the Article "The origin of a child can only be proven by an authentic birth certificate, issued by an authorized official". Meanwhile, in the beleidregels in the form of a Circular Letter of the Director General of Bimas Islam and Hajj Affairs Number D / ED / PW / 01/03/1992 concerning Instructions for Filling Marriage, Talaq, Divorce and Reference (NTCR) Forms for Guardian and Bride Examination Techniques, it is stated in point 1 letter b: "If the first child is to be married and the guardian is the father's guardian, it is necessary to ask when to marry and when to give birth to the first child. If there is any doubt, just five months of marriage and then giving birth to a child then the child is qualified as a mother's child, therefore it is necessary to take the path of takhim (guardian of judges)." This contradiction has not been resolved properly.The approach method used in this study is normative juridical, which is an approach that utilizes legislative concepts. This concept clearly states that the law is the same as the written norms formulated and promulgated by authorized state institutions or officials.This study is a literature study, while the approach method in this study uses a statute approach (legal approach) and a conceptual approach.